Graduate Entrepreneurship and Career Initiation in the 'New Era' Economy. (September 2014) - Rae, David
The aim of this article is to explore graduate entrepreneurship and career-making in the period of stagnant economic growth in the UK over the six years from the financial crisis of 2008 to the present day. In the context of a challenging economy, this period has seen a strong emphasis on graduate employability and education for entrepreneurship within Higher Education, both within the United Kingdom and at international levels. The prevailing employment market offered depressed levels of demand and constrained graduate career opportunities, with signs of recent recovery. The article reflects on six years' experience of this 'New Era', drawing on labour market research and projections, and summarises the challenges and responses in graduate enterprise and employability applicable to the post-2008 economy. Finally, it offers practical options for institutional policies, enterprise education and individual actions, centering on graduate career development.